2017
DOI: 10.1016/j.kjms.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicorandil on renal function and histopathology in rats with partial unilateral ureteral obstruction

Abstract: To evaluate the effects of nicorandil in a rat kidney model of partial unilateral ureteral obstruction (PUUO). Thirty male rats were randomly divided into three groups as follows: (1) Group 1 (Sham-control), ureters of the rats were manipulated but not ligated; (2) Group 2 (PUUO-untreated), PUUO was performed with two-thirds of the left ureter embedded in the psoas muscle; and (3) Group 3 (PUUO-nicorandil treated). After PUUO was established, nicorandil (15 mg/kg/day) was administered by gastric lavage for 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Nicorandil has already been used in the treatment of ischemic heart disease because it could reduce the oxidative stress in the heart failure state. 17 Also, it found to inhibit renal tubular damage and tubulointerstitial fibrosis by reducing the effects of reactive oxygen species (ROS) in a rat kidney model 18 and lead a upregulation of endothelial nitric oxide synthase (eNOS) expression in hypertensive rats. 19,20 Shimizu 21 et al found that the nicorandil treatment could reduce the β2-microglobulin, Scr level in the ischemia–reperfusion injury kidney, and the downregulation of the K-ATP channel was totally prevented after nicorandil treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicorandil has already been used in the treatment of ischemic heart disease because it could reduce the oxidative stress in the heart failure state. 17 Also, it found to inhibit renal tubular damage and tubulointerstitial fibrosis by reducing the effects of reactive oxygen species (ROS) in a rat kidney model 18 and lead a upregulation of endothelial nitric oxide synthase (eNOS) expression in hypertensive rats. 19,20 Shimizu 21 et al found that the nicorandil treatment could reduce the β2-microglobulin, Scr level in the ischemia–reperfusion injury kidney, and the downregulation of the K-ATP channel was totally prevented after nicorandil treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nicorandil has already been used in the treatment of ischemic heart disease because it could reduce the oxidative stress in the heart failure state. 17 Also, it found to inhibit renal tubular damage and tubulointerstitial fibrosis by reducing the effects of reactive oxygen species (ROS) in a rat kidney model 18 22 However, the decreased activity of NOS, increased hydrolysis of ATP, and generation of ROS are also related to the CIN. 23 As mentioned above, the nicorandil has been found to reduce the ROS damage in kidney, induce NO production, and improve the level of eNOS to protect the renal function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in newborn rat showed that nicorandil protects against ischemia‐reperfusion injury of the kidney via decreasing the production of inflammatory cytokines, and restoring the expression of KIR6.2 potentially through the phosphoinositide‐3‐kinase‐Akt‐nuclear factor‐κB axis . In addition, the K‐ATP channel opener has been proved to prevent the accumulation of reactive oxygen radicals (ROS) in mitochondria resulted during the ischemia‐reperfusion injury of the kidney, which is further confirmed by a recent study in a rat kidney model of partial unilateral ureteral obstruction showing that nicorandil can inhibit renal tubular damage and tubulointerstitial fibrosis by reducing the effects of oxidative stress . Furthermore, a previous study in rats received unilateral nephrectomy showed that treatment with nicorandil ameliorated the ischemia‐reperfusion injury of the kidney by restoring the tubular expressions of K(IR) 6.1 and K(IR) 6.2 channels .…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, we found in the present study normalization of the kidney functions and morphology by co-administration of nicorandil with adenine suggesting renoprotective role for nicorandil against adenine-induced nephropathy. This renoprotective effect for nicorandil was shown in rat models of renal I/R injury (Shimizu et al 2011) and partial unilateral ureteral obstruction (Ozturk et al 2017). In addition, Tamura et al (2012) demonstrated the renoprotective effects of nicorandil on a rat remnant kidney model of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, nicorandil (K ATP channel opener) pretreatment caused upregulation of nrf2 in aortic tissues obtained from rats treated with high adenine diet at the level of mRNA suggesting improvement of oxidative stress in aortic tissues might reduce the aortic calcifications. The antioxidant action of nicorandil was demonstrated in a rat model of remnant kidney disease (Tamura et al 2012;Shiraishi et al 2014), rat model of renal I/R injury (Ozturk et al 2017) and brain injury after cardiac arrest in pigs (Zhu et al 2018). Endothelial dysfunctions in chronic kidney disease was demonstrated in high adenine rat model and occurred in the form of imbalance between the vasodilators (serum nitric oxide) and vasoconstrictors (serum endothelin) (Peng et al 2013;Ali et al 2015).…”
Section: Control Control Adeninementioning
confidence: 99%